«Parlare di tutto». Un'idea della critica Il carteggio Baldacci-Fortini - Baldacci, Luigi (Carteggi e materiali del Centro Interdipartimentale di ricerca Franco Fortini, 2023)
This volume presents the correspondence between Luigi Baldacci and Franco Fortini currently preserved in Florence, at the Archivio Contemporaneo Alessandro Bonsanti del Gabinetto Scientifico Letterario G.P. Vieusseux, and in Siena, at the Archivio del Centro Interdipartimentale di Ricerca Franco Fortini. In addition to exchanges on specific authors or events (Noventa, Leopardi, Contini, Papini and the avant-garde, Bontempelli, Aldo Braibanti's trial, etc.), the comparison and in some cases the clash between the two interlocutors pivots on the role of literary criticism in years of a profound cultural crisis and transformation in Italy. Both still place a high value on the figure of the intellectual and of the literary critic, as long as his role is exercised in full awareness of the contradictions that characterize it.